Effect of peer education on self‐management and psychological status in type 2 diabetes patients with emotional disorders. Issue 4 (29th December 2014) - Liu, Yan; Han, Ying; Shi, Jieli; Li, Ruixia; Li, Sufen; Jin, Nana; Gu, Yong; Guo, Honglei
Abstract Aims/Introduction The purpose of the present study was to assess the effect of peer education in type 2 diabetes patients with emotional disorders on the metabolic index and psychological status. Materials and Methods Educators use psychological scales to screen type 2 diabetes patients with emotional disorders. Participants were divided into usual and peer education groups. Both groups received usual diabetes education. Peer leaders were recruited to provide support with the peer education group for 6 months. The metabolic index, diabetes knowledge, self‐management, diabetes‐related distress, emotional status and quality of life were compared at the end of the study. Results A total of 127 patients participated in the study. There were 20 peer leaders engaged in the study as volunteers for peer education. All participants completed the study and fulfilled the scales. Improvements in the peer education group were significant compared with the usual education group with respect to anxiety (49.0 ± 9.65 vs 54.0 ± 8.48), depression (51.3 ± 7.97 vs 55.8 ± 7.52), diabetes knowledge (18.8 ± 2.46 vs 16.3 ± 2.08), distress (2.67 ± 0.55 vs 3.02 ± 0.56), self‐management (66.5 ± 4.26 vs 62.4 ± 5.88) and quality of life (−1.98 ± 0.82 vs −2.50 ± 0.71), whereas no significant difference existed with respect to the metabolic index. Conclusions Peer education, providing more attention to diabetes patients with emotional disorders, is a preferred model for delivering care.